Content on breastfeeding for building an application: interdisciplinary focus group analysis (Research, Society and Development, 2022)
This research aimed to analyze the content about Breastfeeding BF, exposed by specialists who work in Human Milk Banks (HMB), with a view to creating an app to promote breast feeding and the caption of human milk donors. This is a descriptive, exploratory study, with a qualitative approach, in which the focus group technique was used with six specialists working in human bank to produce data. It was identified that the contents for the composition of the app must contain information that helps the woman to maintain breastfeeding and become a donor, such as the benefits of breastfeeding, guidelines that facilitate human breastfeeding and milk donation, the rights that govern BF policy and return to work, as well as support networks and their functions. This content must be exposed with objective language and exploration of visible resources, distributed in the form of tabs including a space for health professionals.